X-ray Emission from Stellar Jets by Collision against High-density Molecular Clouds: an Application to HH 248 - López Santiago, Javier (2015)
Fil: López Santiago, J. Institute of Astronomy and Geophysics, Universidad Complutense de Madrid, España.